Effect of a Simple Collagen Type I Sponge for Achilles Tendon Repair in a Rat Model. (August 2016) - Müller, Sebastian A.; Dürselen, Lutz; Heisterbach, Patricia; Evans, Chris; Majewski, Martin
Background: Several sophisticated approaches to tendon engineering have been investigated as ways to improve tendon healing with the early formation of repair tissue with possibly a high amount of type I collagen. Besides the new formation of collagen type I, there is evidence for the natural integration of surrounding collagen type I from healthy tendon parts into the healing defect. However, the simple application of a type I collagen sponge to the healing site to increase the amount of local collagen type I has not been investigated. Hypothesis: Healing of the rat Achilles tendon can be accelerated by an additional supply of collagen type I, resulting in increased tear resistance. Study Design: Controlled laboratory study. Methods: The right Achilles tendons of 42 rats were transected. In half of the animals, a type I collagen sponge was placed into the gap. Animals were allowed to move freely in their cages to simulate early functional therapy. After 1, 2, and 4 weeks, tendon length, width, maximal load to failure, and stiffness were measured and the healing site studied histologically according to the Bonar score. Inflammation was evaluated by the appearance of macrophages and neutrophilic and eosinophilic granulocytes. Results: Defects receiving collagen sponges showed improved healing, with significantly stronger (29.5 vs 5.0 N, respectively, at 1 week; P = .00003), shorter (11.6 vs 14.5 mm, respectively, at 4 weeks; P = .005), thicker (10.0 vs 1.8 mm 2, respectively, at 1 week; P = .00002), and less stiff (19.5 vs 30.5 N/mm, respectively, at 4 weeks; P = .02) tendons than control tendons. Overall, the biomechanical properties of the collagen-treated tendons appeared to be significantly closer to those of native, uninjured tendons compared with tendons in the control group. Histologically, no inflammatory reaction due to the collagen sponge was found. Conclusion: Tendon healing was accelerated by the type I collagen sponge. Moreover, the mechanical properties of collagen-treated tendons appeared to be significantly closer to those of normal, uninjured tendons compared with control tendons without collagen treatment. Clinical Relevance: As a simple type I collagen sponge seems to increase the amount of local collagen type I, the careful use of such sponges might be an option for tendon augmentation during Achilles tendon surgery.